2002
DOI: 10.1128/mcb.22.11.3875-3891.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of SHP-2 in Fibroblast Growth Factor Receptor-Mediated Suppression of Myogenesis in C2C12 Myoblasts

Abstract: Ligand activation of the fibroblast growth factor receptor (FGFR) represses myogenesis and promotes activation of extracellular signal-regulated kinases 1 and 2 (Erks). The precise mechanism through which the FGFR transmits both of these signals in myoblasts remains unclear. The SH2 domain-containing protein tyrosine phosphatase, SHP-2, has been shown to participate in the regulation of FGFR signaling. However, no role for SHP-2 in FGFR myogenic signaling is known. In this study, we show that stimulation of C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 80 publications
(140 reference statements)
3
59
0
Order By: Relevance
“…5A to F were obtained using bFGF, a known inhibitor of myogenic differentiation (29), instead of S100B; bFGF caused a smaller reduction of MCK induction in L6/RAGE myoblasts than in WT myoblasts, and smaller doses of amphoterin were required to override the antimyogenic effect of bFGF on L6/RAGE myoblasts than were required for WT myoblasts (Fig. 5G and H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A to F were obtained using bFGF, a known inhibitor of myogenic differentiation (29), instead of S100B; bFGF caused a smaller reduction of MCK induction in L6/RAGE myoblasts than in WT myoblasts, and smaller doses of amphoterin were required to override the antimyogenic effect of bFGF on L6/RAGE myoblasts than were required for WT myoblasts (Fig. 5G and H).…”
Section: Resultsmentioning
confidence: 99%
“…Several extracellular factors have been identified that participate in the regulation of myogenesis, some of which promote myoblast differentiation and/or myotube formation, while other factors inhibit these processes. Insulin, insulin-like growth factors (IGF I and IGF II), neuregulin, and nerve growth factor belong to the first category of agents (13-15, 28, 45), while tumor necrosis factor alpha (TNF-␣), basic fibroblast growth factor (bFGF), and transforming growth factor ␤ belong to the second category (12,29,30,35,37,40,42,50,56). However, IGF I and IGF II were reported to promote or inhibit myogenic differentiation depending on the absence or presence of TNF-␣, respectively (16), and down-regulation of nerve growth factor low-affinity receptor was shown to be required for myoblast terminal differentiation (12).…”
mentioning
confidence: 99%
“…To examine whether SHP-2 signals upstream of PLC␤4 in the activation of S6K1, we knocked down PLC␤4 in the presence of a constitutively active mutant of SHP-2 (SHP-2 E76A) (25). Whereas overexpression of SHP-2 E76A enhanced leucine-induced S6K1 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These PTP domain PCR products were subcloned into pGEX-2TK. GST-SHP-2-EA was constructed by PCR amplifying SHP-2-Glu 76 to Ala 76 (EA) described previously (35) and subcloning the product into pGEX-2TK. The NH 2 -SH2 and COOH-SH2 domains of SHP-2 from amino acids 1-215 (GST-NϩC-SH2) have been described previously (36).…”
mentioning
confidence: 99%